Matched: Crossed - Book 2 - Condie, Allyson Braithwaite (New York Dutton Books, 2011)
Seventeen-year-old Cassia sacrifices everything and heads to the Outer Provinces in search of Ky, where she is confronted with shocking revelations about Society and the promise of rebellion.
Keywords: Government, Resistance to -- Juvenile fiction; Government, Resistance to -- Fiction; Fantasy